Effects of Computer Assisted Instruction (CAI) on Academic Performance of Senior Secondary Students in Economics, Kwara State - ADEGBOYE, Surajudeen Olayiwola (Ilorin Journal of Education, 2023)
The computer is one of the greatest inventions of the 20th century which has contributed to the service of humanity through its capacity to automate the highly needed respective earlier discoveries. Therefore, the role of computer cannot be over-emphasized in the current competitive education system. It plays significant role in many aspects of human endeavor. The challenge therefore is to be able to remain relevant in the competitive education system through the adoption and use of modern technology. The research design was quasi experimental using a sample of 120 students, who were assigned into experimental and control groups. The test instrument, Economics Performance Test (EPT) was a 30-item multiple-choice objective test drawn from the past West African Examination Council (WAEC) Senior Secondary Certificate Examination Econmics paper. Also introduced was the treatment instrument, Computer Assisted Instructional Package (CAIP) on Economics. The two groups (experimental and control groups) were subjected to the EPT as pre-test and after the treatment the two groups were rearranged for EPT as post-test. The research questions were answered using mean and standard deviation, while the hypotheses were tested at 0.05 level of significance using t-test analysis. The research finding showed that the use of CAI in teaching Economics will effectively enhance the teaching and learning of the subject more. It was therefore recommended that necessary attention should be accorded CAI as a method of instruction in Economics.